Public Subsidies for Employees' Contributions to Employer-Sponsored Insurance - Mark Merlis (SAGE Publishing, 2001)
Proposals to provide or subsidize health insurance for low-income families must take account of the fact that many workers have access to employer-sponsored insurance (ESI), but decline it because of required employee premium contributions. This article considers a tax credit for the employee share of ESI in the context of a broader program of income-based health insurance tax credits. Helping uninsured workers pay for available ESI could be more cost-effective than subsidizing their coverage in the nongroup market. The credit would also be available to workers who were already covered, both for equity reasons and to reduce the incentives for employers to drop coverage or for workers to shift to subsidized individual plans. One key issue is how to prevent employers from reducing their current health plan contributions to take advantage of the new funding. Other design questions considered by the article include whether workers should be able to choose between ESI and nongroup coverage, whether minimum benefit standards should apply for employer plans, and how to achieve a fair balance in subsidies for group and nongroup coverage.